THE COMPARATIVE OVERVIEW OF HPLC ANALYSIS OF DIFFERENT EXTRACTS FROM MORUS SPECIES FROM SOUTHEAST SERBIA - DIMITRIJEVIĆ, Danica; KOSTIĆ, Danijela; MITIĆ, Milan; PAUNOVIĆ, Dušan; STOJANOVIĆ, Branka; KRSTIĆ, Jovana; STEVANOVIĆ, Slavica; VELIČKOVIĆ, Jasmina (Studia Universitatis Babeș-Bolyai Chemia, 2020)
The aim of this work was to evaluate the content of phenolic compounds (phenols, flavonoids and anthocyanins) of Morus alba L. fruit (white mulberry), Morus rubra L. (red mulberry) and Morus nigra L. fruit (black mulberry) by the HPLC analysis. In the extracts of white, red and black mulberry identified the four phenolic acids by HPLC analysis: chlorogenic, 4-caffeoylquinic, 5-caffeoylquinic and caffeic acid. 5-caffeoylquinic acid was identified in all tested extracts of white, red and black mulberry. 4-caffeoylquinic acids contain all the extracts except methanol extract of red mulberry. Caffeic and chlorogenic acid containing methanol extracts of white and red mulberry.